(untitled) (Medical Forum Monthly, 2023)
Objective: The main objective of the study to find out the relationship between team behaviors characteristics and team performance. This article is helpful to explore the relationship between team behavior, characteristics and performance of the in terms of role clarity, openness to change, goal motivation and cohesion. Study Design: Observational / descriptive / cross sectional study Place and Duration of Study: This study was conducted in Global Institute (CFE Campus) Lahore from January 2015 to July 2015. Materials and Methods: Samples were collected from the medical directors of public and private hospitals of Lahore. Questionnaire was conducted in the form of closed ended question. Survey was conducted from June. During the survey, overall 35 questionnaires were distributed. Participant responded the questionnaire on scale of 1 to 5. Results: The overall adjusted R-square is (0.739) its mean that the team performance is 73.9% depends upon these factor in this research we also analysis the factor individually. Cohesion is only variable that contributes only (0.100) 10%, Role Clarity (0.421) 42.1%, Goal Motivation (0.403) 40.3% and openness to change is (0.264)26.4% respectively. All the variables are highly significant other than cohesion. Conclusion: Medical Directors of Public & Private Hospitals are agreed with the statement regarding team performance, role clarity, goal motivation, openness to change.